2018
DOI: 10.3389/fphar.2018.00179
|View full text |Cite
|
Sign up to set email alerts
|

Can a Conversation Between Mesenchymal Stromal Cells and Macrophages Solve the Crisis in the Inflamed Intestine?

Abstract: Inflammatory bowel disease (IBD) is a group of chronic inflammatory conditions of the gastrointestinal tract characterized by an exacerbated mucosal immune response. Macrophages play pivotal roles in the maintenance of gut homeostasis but they are also implicated in the pathogenesis of IBD. They are highly plastic cells and their activation state depends on the local environment. In the healthy intestine, resident macrophages display an M2 phenotype characterized by inflammatory energy, while inflammatory M1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 130 publications
(158 reference statements)
0
24
0
Order By: Relevance
“…In this sense, these studies have demonstrated that non-classical CX3CR1 + monocytes, CCR2 + monocytes, or bone marrow monocyte precursors were the progenitors of regulatory macrophages that were responsible for wound healing after intestinal injury. 33 , 34 , 44 Additionally, Quinn et al described that the inflammation induces monocyte migration and accumulation of AAMs in the peritoneal cavity which then migrate and differentiate into tissue macrophages, inducing tolerance in the long term. 45 They also suggested an immunological memory induced by the innate immune system.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, these studies have demonstrated that non-classical CX3CR1 + monocytes, CCR2 + monocytes, or bone marrow monocyte precursors were the progenitors of regulatory macrophages that were responsible for wound healing after intestinal injury. 33 , 34 , 44 Additionally, Quinn et al described that the inflammation induces monocyte migration and accumulation of AAMs in the peritoneal cavity which then migrate and differentiate into tissue macrophages, inducing tolerance in the long term. 45 They also suggested an immunological memory induced by the innate immune system.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines directly or indirectly affect the intestinal epithelial cells, leading to the injury or necrosis of these cells, which promotes the occurrence and development of IBD ( Figure 1 ). An over-secretion of cytokines and chronic inflammation are the typical features of IBD, with clinical symptoms of diarrhea, abdominal pain, fever, intestinal obstruction, and disability symptoms of blood or mucus or both ( Baumgart and Carding, 2007 ; Geremia et al, 2014 ; Geremia and Arancibia-Cárcamo, 2017 ; Hidalgo-Garcia et al, 2018 ; Ding et al, 2019b ). IBD occurs exclusively in the colon in ulcerative colitis and almost anywhere along the gastrointestinal tract in chronic diarrhea ( Jones et al, 2018 ).…”
Section: Intestinal Inflammationmentioning
confidence: 99%
“…The largest population of macrophages in the body resides in the gastrointestinal tract, which plays pivotal roles in the maintenance of mucosal homeostasis and is also an important component of protective immunity 2 . M1 macrophages can release inflammatory cytokines to induce an inflammatory response.…”
Section: Introductionmentioning
confidence: 99%